Managers’ Strategies to Support Employee Well-Being in Remote Work Environment - Kukytė, Aistė (Vilnius University Proceedings, 2023)
In today’s dynamic environment, employees’ well-being at work has become a matter of concern not only to employees, business but also to scholars. Workplace well-being relates to how employees feel about their work, their working environment, the climate at work and of course work organisation. Over the past few years in businesses environment numbers of remote workers had increased, thus this change leads to the need for theory and research on how managers can support employees’ well-being in remote work environments. The analysis of the scientific literature allowed to detect aspects of employees’ well-being, reveal managers’ strategies related to supporting well-being at remote work. Based on the obtained results and scientific literature review, the conceptual model of managers’ strategies to support employees’ well-being in remote work environments is presented
Keywords: well-being; remote work-related well-being; managers’ support for remote employees